Stomach Content Analysis of Ompok hypophthalmus from the Tarai River, Tarai Bangun Village, Tambang District, Kampar Regency, Riau Province - Eka Sahriani; Windarti Windarti; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Ompok hypophthalmus is one of freshwater fish that inhabit the Tarai River. To understand the type of food consumed by O.hypophthlamus, a study has been conducted on April-June 2018. The fish was captured using a gill net and a scoop net. There were 105 fishes captured, that was consisted of 77 fishes with filled stomach and 28 fishes with empty stomach. Stomach content of the fish was analyzed as a basis to calculate the Preponderance Index (IP). Results shown that TL of the O.hypophthalmus ranged from 72 to 211 mm and BW ranged from 2.31 to 45.32 gram. The main food of O.hypophthlamus was insects (53%), the complementary food was fish (21%), and the additional food was unidentified debris (10%), molusca (9%), and crustacean (7%). Keywords :Sheatfish, fish food, Index of Preponerance, Carnivore fish